1-Methylcyclopropene and lemongrass essential oil nanocoatings effect on the preservation of cold stored ‘Rocha’ pear - Gago, Custódia (2022)
The effects of coating 'Rocha' pear with alginate-based nanoemulsions enriched with lemongrass essential oil (LG) was evaluated and compared to the usual 1-MCP treatment. Fruit were treated with 1-MCP (312 nL L-1) or coated with nanoemulsions: sodium alginate 2 % (w/w) + lemongrass essential oil 1.25 % (w/w) (LG 1.25 %) or lemongrass essential oil 2.5 % (w/w) (LG 2.5 %). Then, fruit were stored at 0 degrees C and 90-95 % relative humidity (RH), for eight months. Fruit samples were collected at harvest and after two, four, six and eight months of cold storage, and then transferred to shelf-life at 22 degrees C. Upon removal and after 7 d shelf-life, fruit symptoms of superficial scald and internal browning, ethylene production, color CIE (L*, hue), firmness, soluble solids content (SSC), titratable acidity (TA), weight loss, electrolytic leakage (EL), antioxidant activity and fatty acids of pear peel, microbial growth and sensory analyses were evaluated. Coatings and 1-MCP reduced fruit color evolution and preserved better firmness than control. Coatings and 1-MCP did not affect SSC and TA. Treatments did not influence the sensory quality. Microbial growth was within the safety limits in all treatments. Treatments with 1-MCP and LG-nanoemulsions were similarly efficient to reduce superficial scald, nevertheless the LG-nanoemulsions showed higher internal disorders after 8 months of storage and LG 2.5 % had higher decay at the same period, similar to control. 1-MCP treated fruit had the lowest softening rate after shelf-life up to 4 months and LG 2.5 % showed higher weight loss. Also, ethylene production was higher in control and LG 1.25 % up to 6 months plus shelf-life, while after 8 months there was no difference among treatments. This study suggests that 1-MCP is the most efficient for preserving quality of 'Rocha' pear for 8 months, while up to 6 months the best effect is obtained with LG 1.25 % nanocoatings.